PSYCHOSOCIAL ROOTS OF CORRUPTOGENIC BEHAVIOR IN PUBLIC ADMINISTRATION (Scientific journal of the Fergana State University, 2026)
This article analyzes the causes behind the manifestation of corruption-prone tendencies in management cadres. It discusses social and psychological factors, the human capabilities of personnel, and the weaknesses within the internal system of state governance that contribute to the growth of corruption. The authors identify key factors such as personnel policies, the psychological state of leaders, the lack of social responsibility, and injustices within the governance processes as major contributors to corruption. The article emphasizes the importance of social-psychological factors in developing effective anti-corruption strategies and provides recommendations for improving the governance system.